Benign intradermal melanocytic naevus with osteoclast-like giant melanocytes: a case report of an unusual morphological pattern. Issue 1 (January 2023) - Toss, Michael; Issa, Hiba; Colver, Graham; Al-Omari, Ali
Abstract: Multinucleated osteoclast-like melanocytes are a relatively common feature in malignant melanoma, however reported cases of benign melanocytic naevi with giant cells melanocytes are scarce. Herein, we present an unusual case of an intradermal melanocytic naevus with numerous benign giant cell melanocytes. A 42-year-old female presented with a small papule on the forehead which was excised. Histologically, the lesion was formed of an intradermal proliferation of benign melanocytes without junctional activity. The melanocytes were arranged in small nests and showed neither cytological atypia nor mitotic activity. There were numerous multinucleated osteoclast-like giant cells with abundant eosinophilic granular cytoplasm and several small open face nuclei. These multinucleated cells showed immune reactivity to melanocytic markers. This case represents a rarely described morphological pattern of a benign intradermal melanocytic lesion showing multiple benign giant cell melanocytes. Reporting such a case provides further evidence to support the presence of this morphological entity and would aid in further understanding its biology and clinical significance.